The equity premium puzzle and emotional asset pricing - Marc Gürtler; Nora Hartmann (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2004)
Since the equity premium as well as the risk-free rate puzzle question the concepts central to financial and economic modeling, we apply behavioral decision theory to asset pricing in view of solving these puzzles. U.S. stock market data for the period 1960-2003 and German stock market data for the period 1977-2003 show that emotional investors who act in accordance to Bell's (1985) disappointment theory - a special case of prospect theory - and additionally administer mental accounts demand a high equity premium. Furthermore, these investors reason a low risk-free rate. However, Barberis/Huang/Santos (2001) already showed that limited rational investors demand a high equity premium. But as opposed to them, our approach additionally supports dividend smoothing.
Keywords: G12; G35; 330; Behavioral Finance; Equity Premium Puzzle; CCAPM; Dividend Smoothing